2016
DOI: 10.1002/polb.23983
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of pulse responses of lithium salt‐doped poly ethyleneoxide

Abstract: Ionic migration in organic electrolytes resembles that in neural system involving signal transportation. Here, ionic dynamic simulations are applied to explore pulse responses of lithium‐doped polyethyleneoxide complexes. Two main interactions were considered: diffusion of ions and directional movement guided by an applied electric field. Frequency responses are simulated using arbitrary wave shape. It is found that redistribution of ions results in accumulation of charge and establishes a reverse inbuilt elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The latter then resulted in variation of the absolute values of synaptic weight and the threshold frequency of transition from depression to potentiation . Besides, we have demonstrated the ionic kinetic origin of the simple potentiation microscopically, and also suggested that the ionic migration during the period of an input pulse might contribute to the bidirectional signal transferring …”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…The latter then resulted in variation of the absolute values of synaptic weight and the threshold frequency of transition from depression to potentiation . Besides, we have demonstrated the ionic kinetic origin of the simple potentiation microscopically, and also suggested that the ionic migration during the period of an input pulse might contribute to the bidirectional signal transferring …”
Section: Introductionmentioning
confidence: 66%
“…We suppose that these modifications might be the physical mechanisms to select signal strength and routine adaptively under the multidomains system. We have adopted a microscopic model to well simulate pulse responses of Li‐PEO . The activation of more domains at HFS might involve in mechanical modifications of electrolyte molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that ionic migrations in organic semiconductor and/or electrolyte heterogeneous junctions possess features in common with those in the macromolecules of biological neural networks, particularly in the aspect of responses to electrical stimulations. [1][2][3][4][5][6][7][8] Frequency selectivity was found in an organic semiconducting polymer/electrolyte heterojunction device, i.e., the semiconducting polymer/electrolyte device responded to low-frequency pulses in depression and to high-frequency pulses in potentiation. 9,10 A modulation of the semiconducting layer could realize long-term plasticity (memory) from short-term plasticity, 6,11 i.e., conventional spikerate-dependent plasticity (SRDP), a widely discussed learning protocol in neuroscience.…”
Section: Introductionmentioning
confidence: 99%